Fabrication and characterization of highly ordered SiPt-CuO nanoarray - Liu, Chao. (2013)
Copper oxide (CuO) has been extensively studied recently due to its unique properties and diverse applications. Nanostructured CuO is thought to be a promising material in the development of non-enzymatic glucose sensor. Among all, shape-controlled synthesis of perfectly ordered CuO nanostructures has received great attention in both chemistry and material science. This is because the ordered arrays show its potential applications in many different fields.